استفادة برنامج الخطابة في إثراء مفردات لدى طلاب معهد الفتح الإسلامي - Amien, Muhammad Faizul; Makruf, Imam; Mubarok, Alfian (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
This study aims to describe and determine the role of the Arabic speech program in enriching students' Arabic vocabulary at the Al-Fatah Islamic Boarding School in Cilacap, Central Java. This study used a descriptive quantitative method, involving 20 randomly selected high school students. Data were collected through interviews, observations, and questionnaires before and after the program. The results showed that 1) the utilization of the khitabah was carried out through structured and interactive preparation and implementation, which encouraged students to not only listen but also speak in Arabic. The use of clear pronunciation, attention to phonetics, and audience involvement helped improve learning outcomes, and 2) vocabulary mastery increased to 91.3%. The speech program also contributed to students' grammatical awareness and sentence construction skills. This study concluded that the Arabic speech program is a very effective strategy in teaching Arabic as a foreign language, especially in improving vocabulary.